Frequency of JAK2 and MPL Mutation in BCR/ABL Negative Myelofibrosis in KPK - Ayesha Gul, Sheeba Ishtiaq, Hina Umair, Memoona Rasheed, Ayesha Gul, Sheeba Ishtiaq, Hina Umair, Memoona Rasheed (Journal of Rawalpindi Medical College, 2022)
Introduction: BCR-ABL1-negative myeloproliferative disorders are a sub-group of myeloproliferative neoplasms (MPNs) that consist of polycythemia Vera (PV), Essential thrombocythemia (ET) and Primary Myelofibrosis (PMF). Over the past decade, the morphological and clinical division of myeloproliferative neoplasms (MPN) has changed to a classification that describes the molecular heterogeneity and is unique to this subgroup of haematological malignancies. This includes alterations in Janus kinase 2 (JAK2), and MPL genes. Objective: To determine the frequency of JAK2 (p.V617F) and MPL (p.W515L) mutation in primary myelofibrosis in KPK province of Pakistan. Methodology: Fifty patients with PMF were enrolled in the study. JAK2 mutation status was determined using allele specific primers and MPL mutation was detected by direct Sanger sequencing technique. The data was analyzed using BioEdit by aligning the sequence data with reference genome hg19 assembly. Results: Among 50 patients, 41 patients were diagnosed with PMF, while 9 patients had secondary myelofibrosis i.e. Post PV-MF and Post ET-MF. Out of the 41 PMF patient 2 patients had MPL gene variation, while one of the Post ET –MF had a MPL gene variation. Forty eight (96%) were positive for JAK2 mutation. Five patients who had MPL mutation also showed JAK 2 mutation. Two of the MPL positive patients were also positive for JAK2 mutation. Conclusion: We reported rate of recurrence of JAK2 mutation in 96% of the cases and MPL exon 10 mutations in 6% of the cases. Keywords: JAK2, MPL, Myeloproliferative neoplasms.